The Strategic Classification Of Leadership Positions In Organizational Management - Abdul Wahid Mahsuni; Ihsan Zikri Ulfiandi; Abdul Hadi; Dodi Erwin Prasetyo; M. Alfan Rikza (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Leadership is a crucial element in determining the effectiveness of an organization, including within higher education institutions. This study aims to analyze the classification of leadership positions based on three management levels top-level, middle-level, and lower-level management and their implementation at STIE PEMNAS Indonesia Malang, a small higher education institution. The research employs a qualitative descriptive approach with a case study method, using data collection techniques such as observation, semi-structured interviews, and documentation involving nine informants, including institutional leaders, program heads, and administrative staff. The findings reveal that the leadership structure at STIE PEMNAS reflects a clear division of roles and responsibilities consistent with the theory of Robbins and Coulter (2016). However, horizontal coordination among departments remains limited due to resource constraints. Empirical data indicate that vertical communication between leadership levels is effective, with 73% of respondents perceiving leadership performance positively. The study also found that some positions involve multiple overlapping roles due to the small organizational scale. This study concludes that clear role delineation, open communication, and leadership training for middle- and lower-level management are essential to enhance organizational effectiveness. The findings are expected to serve as a reference for improving governance and leadership structures in small-scale higher education institutions in Indonesia.